Notaries at Risk: Urgent Need for Legal Protection Against Criminal Acts: Notaris Berisiko: Kebutuhan Mendesak akan Perlindungan Hukum Terhadap Tindak Pidana - Setiawati, Yuni; Salim, Lendra Akbar; Melati, Ayu Sekar; Chesar, Wery (Rechtsidee, 2023)
This study aims to address the legal protection issues faced by notaries in relation to potential criminal acts and proposes ideas for regulating legal protection. Utilizing a normative legal research approach, data was collected through literature reviews, document analysis, and legal interviews, with conceptual and legal framework analysis conducted. The results reveal a lack of legal harmonization between notarial law and criminal law, which challenges the provision of adequate legal protection for notaries. Harmonization of legal provisions is critical to ensure optimal notarial services and protect against potential criminal acts. The findings emphasize the urgency of implementing legal provisions for notaries' adequate protection and offer valuable insights for policymakers and legal practitioners in crafting effective legal frameworks. Highlights: Legal harmonization between notarial and criminal law is needed for adequate protection of notaries. Protection is necessary for optimal services and protection against criminal acts. Harmonizing legal provisions is critical for effective protection. Keywords: Notarial Law, Legal Protection, Criminal Acts, Harmonization, Professional Duties